DESENVOLVIMENTO E AVALIAÇÃO DE MICROPARTÍCULAS POLIMÉRICAS CONTENDO RESVERATROL - Mendes, Jessica Bitencourt Emilio (2011)
Resveratrol is a potent antioxidant, anti-inflammatory, anticancer, and chemoprotective agent. However, it is sensitive to some external agents such as air, light and oxidative enzymes that can reduce its viability and bioavailability for clinical use. In order to provide a controlled release, the aim of this study was to obtain resveratrol-loaded polyester microparticles and to evaluate their physicochemical properties, antioxidant potential and effect on hemolysis of human erythrocytes. Microparticles of poly(3-hydroxybutyrate-co -3-hydroxyvalerate) (PHBV) and poly(-caprolactone) (PCL) containing resveratrol were successfully prepared by simple emulsion/solvent evaporation. All formulations showed suitable encapsulation efficiency values higher than 80%. PHBV microparticles revealed spherical shape with rough surface and presence of pores. PCL microparticles were spherically shaped with smooth surface. Fourier-transformed infrared spectra demonstrated no chemical bond between resveratrol and polymers. X-ray powder diffraction patterns and differential scanning calorimetry analyses indicated that microencapsulation led to a drug amorphization. These PHBV/PCL microparticles delayed the dissolution profile of resveratrol. Release profiles were better fitted to biexponential equation. The hypochlorous acid scavenging activity and 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation decolorization assay confirmed that the antioxidant activity of resveratrolloaded into PHBV/PCL microparticles was kept, but was dependent on the microparticle morphology and dissolution profile. Resveratrol-loaded PHBV/PCL microparticles showed no cytotoxic effect on red blood cells. These results support an experimental basis for the use of resveratrol-loaded PHBV/PCL microparticles as a feasible oral drug delivery carrier for controlled release of resveratrol, being an attractive alternative in chronic diseases prevention.